Symptoms associated with menopause and its relationship to quality of life among a sample of women in Zarqa Governorate - Tarawneh, Amany Waheed Shaher (Journal of Educational and Psychological Sciences, 2021)
The aim of the current research is to identify the relationship between symptoms associated with menopause in women and the quality of life they have from their point of view, and the study sample consisted of (200) women who frequent the Khouli Bint Azwar Association in Zarqa Governorate, during the period between (1/1/2020) - 6/30/2020). The descriptive and analytical approach was followed and the questionnaire was used as a tool to collect data. The results of the study showed that the quality of life of adult menopausal women was of a moderate degree, and the results of the study indicated a negative correlation between menopause and the quality of life of the research sample. The research came out with a set of recommendations, the most important of which are: the need to educate and educate women about the topic of menopause, how it occurs, its causes, and deal with it through holding meetings and dialogues aimed at introducing women to the stage of menopause before reaching their age.
Keywords: menopause; quality of life; women; Jordan